The Topoi of Mandela's Death in the Arabic Speaking Media: A Corpus-Based Political Discourse Analysis - Mohammed, Tawffeek A. S.; Banda, Felix; Patel, Mahmoud (Frontiers in Communication, 2022)
The present study attempts a political discourse analysis of a spoken Arabic corpus on the death of Nelson Mandela. The corpus mainly consists of the coverage of some Arabic-speaking TV channels that was broadcasted in the aftermath of the announcement of Nelson Mandela’s death in 2014. The discourse-historical approach was employed with a view to finding out the various topoi and ideologies deployed in the corpus. For this purpose, the spoken corpus used in this study was first transcribed using Elan, a transcription tool for multimodal texts. Afterward, the corpus was compiled using Sketchengine to enable researchers to process the data automatically and hence to use different computational tools that can assist in finding the various topoi. A computational analysis using collocations, wordlists, N-gram and concordance features can provide a more precise analysis of these various topoi in context and hence to uncover the ideologies of participants/politicians. The findings of the study showed that the corpus abounds in topoi that are not necessarily related to Mandela or his death, but they are rather related to heated political issues in various countries of the Middle East. Politicians have shifted their focus from the main topic which is the death of Nelson Mandela to conflicts and political plights in countries such as Egypt, Syria, Iran, Iraq, Yemen, and Palestine. Politicians have used the media coverage as a platform to express their feelings and to compare Mandela with the Arab leaders in their respective countries. The coverage has sometimes transcended speaking about Mandela to the deployment and projection of certain ideologies of the interviewees. Those ideologies are not only confined to one participant's country, but they are representative of the Arab identity and concerns at large.